Risk factors for heterotopic ossification in operatively treated proximal humeral fractures. (April 2020) - Cirino, Carl M.; Chan, Jimmy J.; Patterson, Diana C.; Jia, Rachel; Poeran, Jashvant; Parsons, Bradford O.; Cagle, Paul J.
Abstract : Aims: Heterotopic ossification (HO) is a potentially devastating complication of the surgical treatment of a proximal humeral fracture. The literature on the rate and risk factors for the development of HO under these circumstances is lacking. The aim of this study was to determine the incidence and risk factors for the development of HO in these patients. Methods: A retrospective analysis of 170 patients who underwent operative treatment for a proximal humeral fracture between 2005 and 2016, in a single institution, was undertaken. The mean follow-up was 18.2 months (1.5 to 140). The presence of HO was identified on follow-up radiographs. Results: The incidence of HO was 15% (n = 26). Our multivariate model revealed that male sex (odds ratio (OR) 3.57, 95% confidence interval (CI) 1.30 to 9.80 compared to female) and dislocation as the initial injury (OR 5.01, 95% CI 1.31 to 19.22) were significantly associated with the formation of HO (p < 0.05) while no significant associations were seen for the age of the patient, the characteristics of the injury, or the type of operative treatment. Conclusion: This retrospective radiological study is the first to investigate the association between the method of surgical treatment for a proximal humeral fracture and the formation of HO postoperatively. We found that male sex and dislocation as the initial injury were risk factors for HO formation, whereas the method of surgical treatment, the age of the patient, and the pattern of the fracture were not predictive of HO formation. While additional studies are needed, these findings can help to identify those at an increased risk for HO formation under these circumstances. Cite this article: Bone Joint J 2020;102-B(4):539–544.